2002
DOI: 10.1083/jcb.200111013
|View full text |Cite
|
Sign up to set email alerts
|

Differential PI 3-kinase dependence of early and late phases of recycling of the internalized AT1 angiotensin receptor

Abstract: Agonist-induced endocytosis and processing of the G protein–coupled AT1 angiotensin II (Ang II) receptor (AT1R) was studied in HEK 293 cells expressing green fluorescent protein (GFP)– or hemagglutinin epitope–tagged forms of the receptor. After stimulation with Ang II, the receptor and its ligand colocalized with Rab5–GFP and Rab4–GFP in early endosomes, and subsequently with Rab11–GFP in pericentriolar recycling endosomes. Inhibition of phosphatidylinositol (PI) 3-kinase by wortmannin (WT) or LY294002 caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
150
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 165 publications
(168 citation statements)
references
References 52 publications
(61 reference statements)
16
150
0
2
Order By: Relevance
“…Expression vectors for GFP-Rab7, GFP-Rab5, and GFP-CD63 were previously described. 15,17 Cherry fluorescent protein (CherryFP)-conjugated Rab7 or its dominant negative guanosine diphosphate-locked (GDPlocked) mutant N125I were prepared by recloning the insert from the GFP-conjugated construction into the appropriate vector. GFP-LC3 labels autophagosomes in mammalian cells 18 ; the pEGFP-LC3 expression vector for this chimerical protein was a generous gift from Dr. T. Yoshimori (Osaka University, Japan).…”
Section: Microscopic Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression vectors for GFP-Rab7, GFP-Rab5, and GFP-CD63 were previously described. 15,17 Cherry fluorescent protein (CherryFP)-conjugated Rab7 or its dominant negative guanosine diphosphate-locked (GDPlocked) mutant N125I were prepared by recloning the insert from the GFP-conjugated construction into the appropriate vector. GFP-LC3 labels autophagosomes in mammalian cells 18 ; the pEGFP-LC3 expression vector for this chimerical protein was a generous gift from Dr. T. Yoshimori (Osaka University, Japan).…”
Section: Microscopic Techniquesmentioning
confidence: 99%
“…15,16 Mitotic arrest without overt toxicity was also observed in vacuolar cells. [15][16][17][18] The present experiments aim to characterize the cell morphological and toxic responses to local anesthetics relative to the vacuolar-autophagic state. Novel questions addressed include the clinical relevance of drug concentrations that cause this response and its time frame, the relationship of the vacuolar response to cytotoxicity, the experimental dissociation of the three postulated steps of the vacuolar response ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GFP and HA epitopes have been used to label G protein-coupled receptors, including α 2B -AR and AT1R, resulting in receptors with similar characteristics to the WT receptors [22][23][24]27] were mutated to alanines, were generated using the QuikChange site-directed mutagenesis kit (Stratagene, La Jolla, CA). The sequence of each construct used in this study was verified by restriction mapping and nucleotide sequence analysis (Louisiana State University Health Sciences Center DNA Sequence Core).…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…Subsequent work with intact mammalian cells showed that pharmacologic inhibition of PI 3-kinase by the drugs LY294002 or wortmannin inhibits the intracellular trafficking of receptors, including the recycling of transferrin receptors [12][13][14][15] and the degradation of PDGF receptors [16,17]. A previous study also showed that wortmannin treatment reduces the recycling kinetics of the G protein-coupled angiotensin-1 receptor [18], indicating that postendocytic trafficking of GPCRs might be regulated by phosphoinositides. However, there is no information regarding the dependence of β 2 AR degradation or recycling on PtdIns3P production.…”
Section: Introductionmentioning
confidence: 99%